Health outcome measures in atopic dermatitis: a systematic review of trends in disease severity and quality-of-life instruments 1985-2010. - Balvinder Rehal; April W Armstrong (PLoS ONE)
Background A number of disease-severity and quality-of-life (QoL) instruments have emerged in atopic dermatitis (AD) in the last decade. Objectives To identify trends in outcomes instruments used in AD clinical trials and to provide a useful summary of the dimensions and validation studies for the most commonly used measures. Method All randomized control trials (RCTs) from 1985 to 2010 in the treatment of AD were examined. Results Among the 791 RCTs reviewed, we identified 20 disease-severity and 14 QoL instruments. Of these outcomes instruments, few have been validated. SCORAD, EASI, IGA and SASSAD were the most commonly used disease-severity instruments and CDLQI, DFI, DLQI and IDQOL were the most frequently used QoL measures. Limitations The small number of RCTs using QoL scales makes identifying trends for QoL instruments difficult. Conclusion Overall, there is an increase in the use of disease-severity and QoL instruments in AD clinical trials.